Presupposition Triggers in “The Big Bang Theory Season Nine” Situational Comedy - Nazar Azkhaf; Masriatus Sholikhah (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2017)
This present research is conducted to analyze the types of presupposition triggers performed and to understand the presupposition of the utterances in The Big Bang Theory Season Nine situational comedy. Answering the formulated research question in this research, the researchers used Levinson’s theory (1983) of presupposition triggers. Conducted with the qualitative approach, this present research is designed with the document analysis for the data was analyzed in the form of utterances uttered by the characters as source of data. The subject of this research is a situational comedy entitled The Big Bang Theory Season Nine episode one until five. The result of the research showed the character mostly uttered 11 types of Presupposition from 13 types (Levinson 1983), they are; counterfactual conditionals, temporal clauses, iteratives, change of state verbs, questions, definite descriptions, factive verbs, implicative verbs, comparison and contrasts, verbs of judging, and non-restrictive relative clauses